The Choice Point Model of Acceptance and Commitment Therapy With Inpatient Substance Use and Co-occurring Populations: A Pilot Study - Berman, Brian M.; Kurlancheek, Kris (Frontiers in Psychology, 2021)
Objective(s) Acceptance and Commitment Therapy (ACT) is an empirically supported treatment which aims to enhance self-acceptance and a commitment to core values. The present study examined the effectiveness of the Choice Point model of ACT in a residential substance use disorder (SUD) setting. Choice Point is a contemporary approach to ACT and targets transdiagnostic processes. Methods This uncontrolled quasi-experimental design assessed 47 participants taking part in Choice Point for Substances (CHOPS) in order to investigate its influence on psychological inflexibility, values-based action, and self-compassion over time. The study additionally assessed for sleeper effects and associations between transdiagnostic processes and warning signs of relapse. Results Findings demonstrated a decrease in psychological inflexibility and increases in values-based action and self-compassion over time. Gains were maintained at follow-up, and sleeper effects were observed for psychological inflexibility and mindfulness. Correlational analysis suggested that all transdiagnostic processes were related to warning signs of relapse at follow-up. Conclusion These results provide preliminary evidence for the feasibility, acceptability, and effectiveness of CHOPS for SUD. Observed sleeper effects in psychological inflexibility and mindfulness indicate that CHOPS may provide longer-term benefits critical to a population where relapse is common. While encouraging, these findings should be interpreted with caution. Future research should utilize comparison groups when investigating CHOPS.